The Importance of Planning Intellectually Challenging Tasks - Ali Althuwaybi (Educational Considerations, 2020)
Since the emergence of the 21st century, advances in information, communication, and technology are changing teaching and learning in numerous ways. Today, teachers are essential for this momentum shift. The identification and design of appropriate and effective instructional tasks and applying them in the classroom will affect teaching and learning. However, this goes beyond offering curriculum and teaching materials to educators. Teachers should be able to stimulate passive curriculum materials and transform them into intriguing instructional tasks if they can specify resources, processes, and outcomes. Current literature underscores the need to support teachers in engaging in operational planning activities that allow them to start lessons with mentally stimulating tasks that are proven to encourage more in-depth learning in students. Nonetheless, it is apparent that effective planning of lessons is essential, but its success rests on the application of requisite theories of teaching and learning.
Keywords: Education; Curriculum & amp; Instruction; Educational Leadership; Teaching Methods; Challenging Tasks; Higher Education Administration